URDU-CORRELATIVE STUDY OF QURANIC REGULATIONS AND HADITH MORALS RELATED TO ENVIRONMENTAL PROTECTION AND THEIR CONTEMPORARY SIGNIFICANCE - sadia javaid; Iqra Basheer (دی اسکالر)
The relevance of religious precepts in preserving nature has increased dramatically because of the worsening ecological conditions and the effects of global warming. The present research explores the concepts of ecological responsibility that appear in the Quran and Hadith, assessing their applicability and significance in the modern world. The aim is to clarify the fundamental connection between ecological morality and Islamic teachings, so adding to the conversation on protecting the planet and long-term growth. This study especially attempts to find and analyze Hadith and Quranic passages that highlight the preservation of the environment, evaluate their applicability in the modern era for advancing long-term viability and create strategies for incorporating these lessons into green laws and activities. A qualitative strategy is used, fusing correlative research and analysis of material. The article attempts to show how Islamic ideas can guide and improve preservation of the environmental activities, bridging the disparity between faith-based beliefs and modern environmental habits. The study highlights the theoretical potential of Islamic ecological morals to support worldwide sustainable development goals by placing identified rules within Islamic jurisprudence (fiqh) and legal principles and creating helpful suggestions for decision-makers, theologians, and environmental activists. The overall objective of the research is to promote more environmentally friendly and peaceful coexistence with nature by encouraging Muslim communities and others to recommit to the ecological preservation ideals outlined in the Quran and Hadith.